The Influence of Brand Repositioning and Social Media Communication on Revisit Intention Via Brand Gestalt - Marsela Marsela; Endang Ruswanti; Kemala Rita Wahidi (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
Hospitals need to make various efforts to improve the quality of service in order to attract new patients and retain them. However, retaining existing patients is more difficult than attracting new patients. This study aims to analyze the effect of brand repositioning and social media communication on revisit intention with hospital brand gestalt as an intervening variable at Unimedika Sepatan Hospital, Tangerang. Brand repositioning and communication through social media are important strategies in increasing patient loyalty and intention to reuse hospital services. Hospital brand gestalt, which reflects the patient's holistic perception of the hospital brand, is hypothesized as a factor mediating the relationship between brand repositioning, social media communication, and revisit intention. The research method used is quantitative with a survey approach to 260 respondents who have used Unimedika Sepatan Hospital services. Analyzed using Structural Equation Modeling with the help of AMOS software to test. The results showed that brand repositioning and social media communication significantly positively influenced hospital brand gestalt. Hospital brand gestalt was proven to have a significant influence on revisit intention. These findings indicate that hospital brand gestalt plays a mediating role in the relationship between brand repositioning, social media communication, and revisit intention. The implications of this study emphasize the importance of an effective brand repositioning strategy and the use of social media communication to build positive patient perceptions of the hospital brand, which can increase patient intention to revisit services. Unimedika Sepatan Hospital is advised to strengthen its brand positioning and increase interaction through social media.